Generation of Functional Neutrophils from a Mouse Model of X-Linked Chronic Granulomatous Disorder Using Induced Pluripotent Stem Cells - Mukherjee, Sayandip (Public Library of Science, 2011)
Murine models of human genetic disorders provide a valuable tool for investigating the scope for application of induced pluripotent stem cells (iPSC). Here we present a proof-of-concept study to demonstrate generation of iPSC from a mouse model of X-linked chronic granulomatous disease (X-CGD), and their successful differentiation into haematopoietic progenitors of the myeloid lineage. We further demonstrate that additive gene transfer using lentiviral vectors encoding gp91(phox) is capable of restoring NADPH-oxidase activity in mature neutrophils derived from X-CGD iPSC. In the longer term, correction of iPSC from human patients with CGD has therapeutic potential not only through generation of transplantable haematopoietic stem cells, but also through production of large numbers of autologous functional neutrophils.